A cryptographic one-to-many reversible mapping and it's applications - Hakiem, Nashrul; Siddiqi, Mohammad Umar (2014)
This paper presents a novel mechanism of cryptographic one-to-many reversible mapping between two domains and it's applications. One-to-many reversible mapping is a one-to-many mapping in which the relations can be reversible. Cryptographic one-to-many reversible mapping is that the development of one-to-many mapping is performed based on pseudorandom assignment of the subsets of the other set, such that it is difficult to find the many-to-one reversed relation, in which the assignment is done using cryptographic approach. The one-to-many mapping which generates pseudo-randomly has a high avalanche effect in order to cover the identity. The randomness test is measured in terms of uniformity based on mono-bit tests and avalanche effect based on Hamming distance test. The expected uniformity and avalanche effect value is about 50% of the bits changed has been achieved by using Cipher Feedback mode of Advanced Encryption Standard.